Comprehensive determination of the high-pressure structural behaviour of BaTiO3. Issue 18 (2nd September 2021) - Bull, Craig L.; Ridley, Christopher J.; Knight, Kevin S.; Funnell, Nicholas P.; Gibbs, Alexandra S.
Abstract : We have mapped the phase diagram of BaTiO3 more extensively than previous attempts using high-pressure neutron-powder diffraction. Abstract : We have mapped the phase diagram of BaTiO3 more extensively than previous attempts using high-pressure neutron-powder diffraction. The mapping of the phase diagram has been performed using isothermal compression at fixed temperatures (175, 225, 290, 480 K) within each of the known crystallographic phases, up to ∼6 GPa using a large volume press. The crystallographic structure of each phase has been measured, and the determined absolute atomic displacements of all atoms within the cell have provided detailed information on the order of the phase transitions observed, and the behaviour of the ferroelectric dipole moment.